Early life-history predator-prey reversal in two cyprinid fishes - Marek Šmejkal (Nature Portfolio, 2017)
Abstract Predator-prey relationships are often perceived simply as a situation in which a predator enhances its own fitness while reducing the fitness of its prey. However, this relationship may become reversed when the prey feeds on the juvenile predator stages. We investigated this phenomenon in a model asp (Leuciscus aspius; predator)-bleak (Alburnus alburnus; prey) relationship. The adhesive asp eggs are available for bleak predation after a spawning event for only tens of seconds before they adhere to the stones, where bleak do not forage. Gut content analysis demonstrated that eggs were utilized in high quantities, especially in the spawning peak of the asp reproductive season. Furthermore, using underwater video, we recorded the bleak feeding efficiency on naturally drifting asp eggs as the percentage of eggs eaten. Within the 40 cm egg trajectory captured by our cameras, total egg mortality was 21.2 ± 2.2% on average. The highest survival chances occurred among eggs drifting in aggregations, since the short drifting distance together with their aggregated distribution satiated bleak and part of the egg aggregation could attach to the spawning ground. This study emphasizes the potential efficiency of predator egg utilization by prey, which may have further consequences in predator-prey dynamics.